Extension in Brazilian Higher Education in the context of liquid modernity: an analysis of Resolution CNE/CES no. 7/2018 based on Zygmunt Bauman’s theoretical contributions (Práxis Educativa, 2025)
This article examines extension activities in contemporary Brazilian Higher Education based on Zygmunt Bauman’s theoretical contributions. The author characterizes the present as the era of “liquid modernity,” in contrast to the solid modernity that shaped the traditional university. Methodologically, the study offers a reflection on Resolution no. 7 of December 18, 2018, issued by the National Council of Education/Higher Education Chamber (CNE/CES, acronym in Portuguese), which establishes national guidelines for extension activities in Brazil. The objective was to consider the challenges involved in implementing this resolution in the current context. By introducing the integration of extension into the curriculum, the resolution promotes a civic education committed to the collective good—an ideal that diverges from the individualistic and capitalist logic that predominates in liquid modernity. In this context of tension, the regulation may offer an opportunity for Higher Education Institutions to reaffirm their social mission, countering the fragmentary and market-driven tendencies that shape contemporary education and society.Keywords: Integration of extension into the curriculum. Higher Education. Liquid modernity.